A Look into Electric/Hybrid Cars from an Ecological Perspective. (2015) - Racz, Andrea Aurora; Muntean, Ionuţ; Stan, Sergiu-Dan
Abstract: A worldwide problem today is environmental pollution, resulting in the greenhouse effect, therefore the appearance of eco-friendly cars is a great benefit to the environment. Technology has needed to evolve greatly to be able to power these automobiles over long distances and the process has not ended yet. In this run for evolution and efficiency, there are a lot of questions that still remain open and one of them is what happens at the end of the lifecycle of a battery and an electric motor. As the number of sold electric cars will increase, the amount of electric motors and battery waste will increase too thus leading to a greater impact on the environment. For this reason, in this paper, we present also the negative impact that the mentioned waste will have on the environment to act as a motivation for more research in this field.